Experimental qualification and sensitivity study of antipodal patch antenna structures for orientation independent detection of partial discharges - Kerstin Friebe; Frank Jenau (High Voltage, 2024)
Abstract Partial discharge diagnosis is an important part of monitoring and diagnosing components of the power transmission system. Four different patch antenna structures for the detection of partial discharges are investigated. These patch antennas, which are realisable in a variety of geometric structures, are already the subject of research. They offer the advantage of contactless detection without intervention in the test object or the measuring circuit, and also offer the possibility of alignment independent detection compared to directional antennas. However, it is important and required to examine different structures extensively at the same measurement setup and to compare their performance. To achieve this, four different configurations of patch antenna structures based on basic geometries all in antipodal design are realised: a logarithmic periodic structure, a Hilbert fractal structure and two tapered slot antennas. They are exposed to the same conditions on a special and unique measurement setup. As the main aspect, the performance of orientation independent detection of partial discharges patch antennas with varying distance and rotation in relation to the partial discharge source as well as the operating bandwidth is examined. To rate the structures, an evaluation scheme is created and a sensitivity matrix is generated.